Customers inside, customers outside designing and succeeding with enterprise customer-centricity concepts, practices, and applications - Lowenstein, Michael W. 1942- (New York Business Expert Press, 2014)
Over the past several years, leading companies have entered a period of marketing and operational convergence, or intersection. During this time, those of us who actively follow, and consult in, such trends are witnessing significant multichannel media application (and resultant omnichannel application by consumers), along with more effective and pervasive customer data gathering, analysis, and application, a stronger enterprise-wide focus on customers, and recognition by senior executives that a dedicated high-level function, supported by a team and sufficient resources, is needed to lead and manage the customer experience. One of my business heroes is direct marketing pioneer, adman Les Wunderman. In the late 1960s, speaking about the future of interactive media, customer relationships, and customer experiences, he predicted many of the realities and challenges we are seeing today. The past decade has brought profound changes to consumer decision making and approaches to customer experience and marketing. Significant advances in communication technology are, at the same time, impacting all marketers and enterprises and in a big way. Marketers have to adjust their budgeting, relationship building, omnichannel influence and personalization methods, "Big Data" generation, analytics, and microsegmentation--all while attempting to hit the moving target that is their continuously transitioning customer base.
1. The customer-centric enterprise -- 2. Customer and brand decision making and influence -- 3. Customer behavior measurement -- 4. Big customer data -- 5. Customer strategy and tactics (branding, communications, and relationships) -- Afterword -- Epilogue -- About the author -- Notes -- References -- Index.
Dr. Mary Gretchen F. Chaves (Recommending faculty) : Management Cluster
Includes bibliographical references (pages 125-126) and index.
Keywords: Customer relations; Relationship marketing; advertising; big data; brand; chief customer officer; communication; corporate image and reputation; customer centricity; customer complaints; customer data; customer experience; customer loyalty; employee ambassadorship; employee loyalty; leadership; loyalty program; marketing; performance metrics; relationships; social media; trust; word-of-mouth.